The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1055/s-0042-1759733
|View full text |Cite
|
Sign up to set email alerts
|

The State of Evidence in Prostate Artery Embolization

Abstract: Prostate artery embolization (PAE) has emerged over the past two decades as a minimally invasive, nonsurgical treatment for benign prostatic hypertrophy (BPH). While the majority of evidence for PAE stems from retrospective cohort studies, several seminal randomized controlled trials have been performed comparing short-term outcomes of PAE to transurethral resection of prostate (TURP) and against a sham procedure. Across clinical trials, PAE demonstrates consistent improvement in urological symptoms and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Conversely, PAE has emerged as a compelling therapeutic avenue for the management of LUTS attributed to BPH. PAE not only yields outcomes akin to those achieved through TURP but also mitigates operative risks [ 39 , 40 , 41 , 42 ]. A salient advantage of PAE is its adaptability to prostates exceeding the volumetric threshold of 100 mL, with consistently favorable clinical outcomes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, PAE has emerged as a compelling therapeutic avenue for the management of LUTS attributed to BPH. PAE not only yields outcomes akin to those achieved through TURP but also mitigates operative risks [ 39 , 40 , 41 , 42 ]. A salient advantage of PAE is its adaptability to prostates exceeding the volumetric threshold of 100 mL, with consistently favorable clinical outcomes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Society of Interventional Radiology (SIR), Prostate Artery Embolization (PAE) represents a viable therapeutic avenue for addressing LUTS attributed to BPH, exhibiting comparable efficacy to surgical interventions [ 16 , 39 , 40 , 41 , 42 ]. The allure of PAE is further accentuated by its associated benefits, including reduced hospitalization durations, diminished transfusion risks, and a low incidence of sexual dysfunction [ 16 , 41 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These trials also demonstrated a trend toward fewer adverse events with PAE than with TURP, particularly in terms of sexual dysfunction. 4,5 The most recent American Urological Association guidelines for the management of lower urinary tract symptoms secondary to BPH include PAE, performed by an experienced physician, as a potential treatment option. 2 We agree that PAE can serve as a useful complement to offi ce-based and surgical procedures, and with its addition we are able to offer effective and safe treatment for all patients, irrespective of prostate size, medical comorbidities, or need for anticoagulant or antiplatelet medications.…”
mentioning
confidence: 99%